Late gastrointestinal toxicity after radiotherapy for anal cancer: a systematic literature review. (2nd November 2018) - Pan, Yi Bin; Maeda, Yasuko; Wilson, Ana; Glynne-Jones, Rob; Vaizey, Carolynne J.
Abstract: Introduction: There is a paucity of data on incidence and mechanisms of long-term gastrointestinal consequences after chemoradiotherapy for anal cancer. Most of the adverse effects reported were based on traditional external beam radiotherapy whilst only short-term follow-ups have been available for intensity-modulated radiotherapy, and there is lack of knowledge about consequences of dose-escalation radiotherapy. Method: A systematic literature review. Results: Two thousand nine hundred and eighty-five titles (excluding duplicates) were identified through the search; 130 articles were included in this review. The overall incidence of late gastrointestinal toxicity was reported to be 7–64.5%, with Grade 3 and above (classified as severe) up to 33.3%. The most commonly reported late toxicities were fecal incontinence (up to 44%), diarrhea (up to 26.7%), and ulceration (up to 22.6%). Diarrhea, fecal incontinence and buttock pain were associated with lower scores in radiotherapy specific quality of life scales (QLQ-CR29, QLQ-C30, and QLQ-CR38) compared to healthy controls. Intensity-modulated radiation therapy appears to reduce late toxicity. Conclusion: Late gastrointestinal toxicities are common with severe toxicity seen in one-third of the patients. These symptoms significantly impact on patients' quality of life. Prospective studies with control groups are needed to elucidate long-term toxicity.